Analysis of theatrical scripts applied in the teaching of cryptogames in a Course of Biological Sciences in the City of Fortaleza-CE (Research, Society and Development, 2021)
In Higher Education there is a certain lack of application of didactic methodologies that stimulate and awaken new senses in students. Within this context, the making of theatrical scripts allows students to apply in practice knowledge worked in class in a playful and innovative way. This research aimed to evaluate the suitability of scripts written and staged by students of Morphology and Taxonomy of Cryptogams of the course of Biological Sciences of the State University of Ceará for higher education and/or other school levels. 40 students representing two different semesters participated in the research, which had to elaborate theater scripts related to the botanical contents seen in the subject in focus, then such scripts were analyzed through the methods of SMOG (traditional and adapted) and Flesch. In the traditional SMOG assessment, all scripts were suitable for the university public, except "E da água brotou" which also applied to high school students; in the adapted version of SMOG, only the scripts "Briófitas do sertão" and "Charles Jones: em busca da pteridófita perdida" were suitable for the university public, and the others at the high school level, and "E da água brotou" for junior high school. On the Flesch scale, the reasonably easy level of readability predominated. The scripts proved to be appropriate for the public and easy to read, which evidences the relevance of the use of this technique for teaching and learning in any age group, thus being an enriching activity resulting from activities developed with the Practice as a Curriculum Component, a mandatory component in licenciate courses.